A superposition approach to study slip-flow forced convection in straight microchannels of uniform but arbitrary cross-section - Hooman, K. (International journal of heat and mass transfer, 2008)
This work presents a superposition approach to investigate forced convection in microducts of arbitrary cross-section, subject to H1 and H2 boundary conditions, in the slip-flow regime with further complication of a temperature jump condition assumption. It is shown that applying an average slip velocity and temperature jump definition, one can still use the no-slip/no-jump results with some minor modifications. Present results for slip-flow in microchannels of parallel plate, circular, and rectangular cross-sections are found to be in complete agreement with those in the literature. Application of this methodology to microchannels of triangular cross-section is also verified by comparing the present results with those obtained numerically by undertaking the commercially available software CFD-ACE.